75 - PREDISPOSING CONDITIONS, RISK FACTORS INTRINSIC AND EXTRINSIC PRESENTS IN THE OCCURRENCE OF PRESSURE ULCER (PU) IN THE ELDERLY IN A UNIVERSITY HOSPITAL, NATAL/RN (Fiep Bulletin - online, 2011)
This study aims Identify the predisposing conditions, the risk factors intrinsic and extrinsic in the occurrence of PU in elderly patients hospitalized in a University Hospital of Natal/RN. Descriptive study design with longitudinal and quantitative approach, conducted with 30 patients admitted in various fields of medicine, surgical clinic, neurology and Intensive Care Unit (ICU) of a university hospital in Natal/RN. After approval by the Commission on Ethics in Research of HUOL / UFRN (Opinion No. 135/07) was conducted to collect data from 13/12/2007 to 20/01/2008, using medical records and structured form. The data were analyzed in SPSS 15.0. Of the 30 patients, developed UP 46.7%, 50.0% are elderly, 57.1% female, 50% admitted from 7 to 18 days in ICU and wards (57.1%). The main regions of PU were sacral (85.7%) and trocantérica (28.6%). The PC, IF and EF were more present in the elderly, being the main predisposing conditions: use of analgesics (64.3%), haematological and psicogênicas (57.1%), cardio-respiratory, metabolic, and nutritional use of anxiolytics (42.9%); intrinsic factors: changes in texture (64.3%), temperature, turgor and elasticity of the skin and mobility impaired physical part (57.1%); extrinsic factors: pressure from the body, lifting the head ? 30 degrees, conditions of bed linen and mobility inadequate (even decubitus> 2h) (64.3%); type of mattress inadequate (57.1%); partial restriction of movement and strength of shear / friction (42.9%) . The weaknesses and fragility of the elderly population contribute to change the lifestyle of the elderly, compromising the sensory perception, activity, mobility, nutrition and characteristics of the skin, requiring assistance more effective and focused in preventing the PU and its complications are responsible by increased morbidity and mortality and costs during hospitalization.
Keywords: Pressure Ulcer; Aged; Risk Factors